Formulation of nanoparticles from short chain chitosan as gene delivery system and transfection against T47D cell line - Lina Winarti; Ronny Martien; Sismindari . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Recently numerous prototype DNA-based biopharmaceuticals can be used to control disease progression by induction and inhibitin the overexpression of genes. Since there are poor cellular uptake and rapid in vivo degradation of DNA-based therapeutics therefore the use of delivery systems to facilitate cellular internalization and preserve their activity is necessary. Cationic polymers commonly used as carriers to delivery gene because of easy to form complexes and higher stability compared to that lipoplexs. Chitosan, a cationic, are polymer most widely used in gene delivery systems because of the low toxicity, and biocompatible. The aim of this study was to formulate nanoparticles of short chain chitosan-pEGFP-C1 and short chain chitosan/TPP-pEGFP-C1 by coaservation complex method. Stability test of the formula was performed by incubating the nanoparticles complex with DNase I and Artificial Intestinal Fluid. Cytotoxicity and transfection studies were evaluated against T47D cell line. The diameter of Chitosan-pEGFP-C1 and chitosan/TPP-pEGFP-C1 nanoparticles were on the range of 56–282.8 nm. The zeta potential wasdetermined to be +14.03 - +16.6 mV. Stability studies showed that chitosan-pEGFP-C1 and chitosan/TPPpEGFP-C1 nanoparticles were stable, undegradable by DNase I and artificial intestinal fluid. Cytotoxic Assay of Chitosan-pEGFP-C1 and chitosan/TPP-pEGFPC1 nanoparticles (pH 4.0) showed that the viability of cell was > 90% for all formulas. EGFP-C1 plasmid gene delivered by chitosan nanoparticles can be expressed in T47D cell culture. According to these results chitosan and chitosan/TPP nanoparticles had potentially to be used as a non-viral vector system delivery for gene therapy.Key words:Chitosan, Nanoparticles, Plasmid EGFP-C1, Cell culture T47D